Islamic Religious Education As A Means Of Internalizing Tolerance Values In The Era Of Multicultural Society In Bumi Mas Village - Intan Rugkiyanisa; Dedi Setiawan; M.Sayyidul Abrori (Journal of Research in Islamic Education, 2026)
This study aims to examine the role of Islamic religious instruction in promoting tolerance within the multicultural community of Desa Bumi Mas. The research is grounded in the social reality that, although interreligious relations in the village are generally peaceful, the internalization of tolerance through Islamic religious instruction has not yet been fully developed. Several issues were identified, including residents’ difficulty in accepting differing opinions, the presence of relatively exclusive religious perspectives, and the tendency for tolerance to be shaped more by long-standing social and cultural habits rather than by a deep understanding of Islamic teachings. This study employs a qualitative method using a case study approach. Data were collected through interviews with religious leaders and community figures, observation of religious and social activities, and documentation. The findings show that Islamic Religious Education in Desa Bumi Mas functions as a medium for the transformation, transaction, and internalization of tolerance values within the community. Through various religious activities such as study gatherings, sermons, and community social activities, religious leaders convey values of tolerance including good moral character, mutual respect, maintaining harmony, and not forcing beliefs on others. These values are not only communicated through one-way teaching but also through two-way interactions between religious leaders and community members in activities such as mutual cooperation and village deliberations. Through this process, tolerance values are gradually internalized in community life, as reflected in the peaceful coexistence of residents despite differences in religious backgrounds. However, some community members still perceive tolerance mainly as a social habit, indicating the need for continuous Islamic religious guidance to strengthen tolerance as an integral part of religious values.